2007
DOI: 10.1182/blood.v110.11.1030.1030
|View full text |Cite
|
Sign up to set email alerts
|

PHA-739358, an Aurora Kinase Inhibitor, Induces Clinical Responses in Chronic Myeloid Leukemia Harboring T315I Mutations of BCR-ABL.

Abstract: Background. The T315I BCR-ABL mutation confers high level resistance to clinically available ABL kinase inhibitors (i.e., imatinib, nilotinib, dasatinib, bosutinib, INNO-406). PHA-739358 is an aurora kinase inhibitor that selectively inhibits the ATP site of Aurora-A, Aurora-B and Aurora-C kinases, and binds with high affinity to both wild type Abl and Abl/T315I in vitro. A multicenter phase II study of PHA-739358 is being conducted in patients with chronic myeloid leukemia (CML) relapsing on imatinib or other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The CP-CML patient also had a minor cytogenetic response, and the AP-CML patient had a CCyR and a CMR. 95 Additional studies are reportedly ongoing to explore alternative dosing schedules.…”
Section: Pha-739358 (Nerivano Medical Sciences Milan Italy)mentioning
confidence: 99%
“…The CP-CML patient also had a minor cytogenetic response, and the AP-CML patient had a CCyR and a CMR. 95 Additional studies are reportedly ongoing to explore alternative dosing schedules.…”
Section: Pha-739358 (Nerivano Medical Sciences Milan Italy)mentioning
confidence: 99%
“…PHA‐739 358 is a novel small molecule inhibitor which selectively targets BCR–ABL and Aurora kinases A, B and C. PHA‐739 358 demonstrated anti‐proliferative and pro‐apoptotic activity against CML cell lines, wild‐type or IM‐resistant BCR–ABL mutants and primary CD34 + cells derived from CML patients in CP or blast crisis, including those harbouring the T315I mutation 27. A phase II trial with CML patients who have failed IM and/or nilotinib or dasatinib therapy is currently ongoing 28.…”
Section: Myeloid Diseasementioning
confidence: 99%
“…PHA-739358: PHA-739358, a pan-Aurora kinase inhibitor, is currently being evaluated in a multicenter phase II trial. 67 In vitro experiments in cellular assays have shown that the antiproliferative activity of PHA-739358 is partially independent of BCR-ABL1 kinase, because the sensitivity to PHA-739358 is not dependent on BCR-ABL1 mutational status given that similar inhibitory activities were elicited in all imatinib-resistant mutants, including T315I. Preliminary results, reported on 7 patients, showed that 2 of 6 with the T315I mutation experienced response to therapy at a dosage of 330 mg/m 2 .…”
Section: Inno-406: Inno-406 Is An Orally Available Dualmentioning
confidence: 99%